Development of thiolated polyethylene glycol-poly (lactic-co-glycolic acid) co-polymeric nanoparticles for intranasal delivery of quetiapine: in vitro–ex vivo characterization. Issue 9 (13th June 2023) - Patil, Dilip; Nangare, Sopan; Patil, Gaurav; Nerkar, Kalpesh; Patil, Ganesh
Abstract: This study aims to develop quetiapine (QTP)-loaded β -cyclodextrin (β-CD) based co -polymeric thiolated polyethylene glycol-poly(lactic- co -glycolic acid) (t-PEG-PLGA) nanoparticles (QTP@β-CD-t-PEG-PLGA) by transesterification process. As a result, the ex-vivo bioadhesion study shows good bioadhesion because of the thiolation of PEG (t-PEG), which can interrelate through mucin and expand the retention time. In-vitro release study demonstrates the QTP release to 20 h (∼98.76%). Herein, sulfhydryl ligands can form disulfide bonds with cysteine-rich mucus areas that increased the viscosity of mucin and accordingly drug retention. Hence, it can be significant accomplishment for nose to brain drug targeting in psychotic disorder management. Graphical Abstract: UF0001